2008
DOI: 10.1177/0003319708319938
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in Patients with Abnormal Myocardial Perfusion Imaging and Normal Coronary Angiogram

Abstract: A subset of subjects undergoing myocardial perfusion imaging has perfusion abnormalities that are subsequently labeled false positive based on coronary angiography. We evaluated the long-term prevalence of cardiovascular events in these patients. We retrospectively identified 48 patients who had reversible perfusion abnormalities with myocardial perfusion imaging and normal coronary angiography. Patients with known coronary artery disease, left ventricular dysfunction, valvular disease, and cardiomyopathy were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 9 publications
0
14
0
2
Order By: Relevance
“…Embora o FCL possa ser uma consequência de alterações microvasculares, o aumento da resistência microvascular e a aterosclerose generalizada em estágio inicial também demonstraram desempenhar um papel na etiologia. 22,23 Além disso, tentou-se lançar mão das alterações histológicas e patológicas nas artérias coronárias para elucidar a etiologia. Em um estudo conduzido em pacientes com FCL, Mangieri et al, 17 encontraram mudanças, tais como edema celular, hiperplasia fibromuscular, hipertrofia medial, proliferação miointimal, fibrose irregular, lesão capilar e redução do lúmen capilar, resultantes da biópsia do miocárdio, tendo alegado que essas alterações patológicas tornavam o fluxo sanguíneo mais lento através do aumento da resistência vascular.…”
Section: Discussionunclassified
“…Embora o FCL possa ser uma consequência de alterações microvasculares, o aumento da resistência microvascular e a aterosclerose generalizada em estágio inicial também demonstraram desempenhar um papel na etiologia. 22,23 Além disso, tentou-se lançar mão das alterações histológicas e patológicas nas artérias coronárias para elucidar a etiologia. Em um estudo conduzido em pacientes com FCL, Mangieri et al, 17 encontraram mudanças, tais como edema celular, hiperplasia fibromuscular, hipertrofia medial, proliferação miointimal, fibrose irregular, lesão capilar e redução do lúmen capilar, resultantes da biópsia do miocárdio, tendo alegado que essas alterações patológicas tornavam o fluxo sanguíneo mais lento através do aumento da resistência vascular.…”
Section: Discussionunclassified
“…In fact, recent reviews suggest that over 43% of individuals proposed to meet criteria for syndrome x are male sex 3. The Veterans Association (VA) study demonstrated an increase in adverse events among their all-male, predominantly, white cohort 23. In our selection of patients, we found that over 50% of individuals meeting criteria for syndrome x-like disease were male.…”
Section: Discussionmentioning
confidence: 73%
“…However, previous, research has demonstrated that a positive MPS is a significant predictor of adverse events regardless of catheterization findings. 19 Moreover, all diagnostic analyses regarding the DTS in the current investigation must be interpreted with a level of caution given the relatively low positive MPS number, particularly in females. In addition, it would have been advantageous to have included a randomly matched cohort that did not use the handrails during the exercise test to quantify the influence of handrail use on the peak VO 2 discrepancy, which is likely substantial.…”
Section: Discussionmentioning
confidence: 91%